INOVASI SALINMAS SEBAGAI UPAYA RESPONSIVE GOVERNMENT KABUPATEN BANYUMAS DALAM PELAYANAN PENGELOLAAN SAMPAH BERBASIS DIGITAL - Alvian Anggit Pradana; Teguh - Yuwono (Journal of Politic and Government Studies, 2023)
Innovation Salinmas (Banyumas Online Garbage) appears backgrounded by a phenomenon emergency waste that occurs in the Banyumas regency. Something condition Where public produce 600 tons rubbish every day or equivalent with 0.3 kg per person. this cause various type domino effect impact bad happened including trash scattered in every corner city, over volume in place disposal ending, and tails on the occurrence action demonstration public to government. Innovation This based service between pick up rubbish to public like grab or gojek. Study This use formula problem including what innovation is saltmas, how effectiveness innovation salinmas, factor What only determines success innovation salinmas, and how role the actors involved innovation saltmas. Research objectives This is look for know transformation service public after exists innovation this. Analysis study This associated with responsive government efforts as theory service public, theory effectiveness, smart government theory and responsive government theory. Research method This use descriptive qualitative with technique data collection in the form of interview, analysis journal nor documentation. Research results that is innovation saltmas is one proof real responsive district government Banyumas in handle problem waste in Banyumas. Through application this, management waste in the Banyumas regency No Again use method conventional but Already to modern direction, of course with digital method, service public the more easy, cheap, accessible, and fast, so beneficial for society